Dietary fatty acids and incident hip fractures in cohorts of women and men. A relative validation and follow-up study - Eva Warensjö Lemming; Liisa Byberg; Jonas Höijer; Susanna C. Larsson; Alicja Wolk; Karl Michaëlsson (Elsevier, 2024)
Objectives: Hip fractures are associated with a high burden of morbidity and mortality. Diet is essential for preventing fragility fractures, but the role of dietary fatty acids on the risk of hip fracture is uncertain. The aim was to investigate how intake of different dietary fatty acids relates to the risk of hip fracture. A relative validation of the long-term intake of dietary fatty acids estimated from food frequency questionnaires (FFQs) was also performed. Design, settings and participants: We used data collected in two population-based cohorts, the Swedish Mammography Cohort and the Cohort of Swedish men (n = 83,603, 54% men, aged 45-82 years). Data from the repeated investigations in the cohorts and cross-sectional data from their clinical sub-cohorts were used. Measurements: Diet data was collected in FFQs. Incident hip fractures were gathered by individual linkage to national registers. We performed Cox regression analysis to investigate associations between dietary fatty acids and hip fracture. Follow-up time was between January 1st, 1998 and December 31st, 2020. The validation was performed using correlation analyses, comparing fatty acids measured in adipose tissue with estimated fatty acid intakes from FFQs. Results: During up to 23 years of follow-up (mean 18 years) and 1,538,627 person-years at risk, 7345 participants (2840 men) experienced a hip fracture. A low linoleic acid (LA) and high intakes of long-chain n-3 fatty acids were associated with higher hip fracture risk in a non-linear way. In quartile 4 compared to quartile 1 of LA, the multivariable-adjusted hazard ratio of hip fracture was 0.89 (95% Confidence Interval: 0.81, 0.97). The study confirmed the validity of FFQs to capture the intake of the specific dietary long-chain n-3 fatty acids. The estimated intake of LA, α-linolenic acid, and myristic acid were also adequately captured by the FFQs. Validity was confirmed in both women and men. Conclusion: A low to moderate intake of linoleic acid and a higher intake of long-chain n-3 fatty acids were associated with a higher risk of hip fractures. The results indicate that attention should be paid to dietary fatty acid composition for the optimal prevention of fragility fractures.